2023
DOI: 10.1111/pace.14678
|View full text |Cite
|
Sign up to set email alerts
|

Iron and atrial fibrillation: A review

Abstract: Atrial fibrillation (AF), one of the most common arrhythmias in clinical practice, is classified into paroxysmal, persistent, and permanent AF according to its duration. The development of AF is associated with increased cardiovascular morbidity and mortality. However, the exact etiology of this disease remains poorly understood. Recent studies found disorders of iron metabolism might be involved in the progression of AF. Abnormal iron metabolism in cardiomyocytes provides arrhythmogenic substrates through a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Several studies have discovered that a loss-of-function mutation in GATA5 is associated with AF, (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have discovered that a loss-of-function mutation in GATA5 is associated with AF, (11).…”
Section: Discussionmentioning
confidence: 99%
“…Severe cognitive disability, stereotypic movements, epilepsy and cerebral malformation have been linked to mutations and deletions at this locus (30). It's reported that in AF patients with iron overload, interventions in iron metabolism, such as iron chelators and iron removal inhibitors, have been shown to prevent AF by reducing iron mortality (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron deposition in the heart’s atria can have a significant impact on the occurrence and development of supraventricular arrhythmias. Abnormal iron levels can lead to dysregulation of calcium handling, affecting the normal electrical signals, and to changes in the expression and function of ion channels, which regulate the heart’s electrical activity, and promote oxidative stress, creating the electrical and structural remodeling that predisposes to supraventricular arrhythmias [ 51 ]. It has been proven that increased levels of reactive oxygen species (ROS) are associated with atrial fibrillation through changes in both local (atrial cardiomyocytes) and systemic (serum) activity of nicotinamide adenine dinucleotide phosphate oxidase (NOX), an enzyme complex that generates ROS [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TNF- may also promote AF by acting on gap links such as connexin 40,43 (CX40, CX43) [ 86 , 87 ]. One review concluded that TNF- , as one of the hallmark inflammatory pathways of inflammation and oxidative stress in ferroptosis, may interfere with CX40 and CX43 in the atrial gap [ 88 ]. In addition, pinocembrin has also been found to regulate the expression of CX40 and other ion channels in cardiomyocytes by inhibiting inflammation [ 89 ].…”
Section: The Role Of Ferroptosis and Inflammation In Afmentioning
confidence: 99%